The Influence of Business Capital and Entrepreneurship Behavior on The Success of Furniture Business in Bayat District Klaten Regency - Marsudiyanti, Esti; Suwandi, Joko; Narmanditya, Bagus Sandy (Proceedings International Conference on Education Innovation and Social Science, 2023)
The purpose of this study was to determine the effect of business capital and entrepreneurial behavior partially and simultaneously on business success in Bayat District, Klaten Regency. Research with a quantitative type uses a descriptive research design. The population of furniture entrepreneurs in Bayat District is 20 furniture entrepreneurs. The research sample for furniture entrepreneurs in Bayat District, Klaten Regency was 20 furniture entrepreneurs. The data collection method used a questionnaire and was analyzed using multiple linear regression analysis with the help of the SPSS 29.0 for Windows program. The results showed that there was no effect of business capital on business success as indicated by the probability value of the t test which was 0.356 which was greater than α = 0.05, there was an influence of entrepreneurial behavior on business success as indicated by the probability value of the t test of 0.001 which was smaller than α = 0.05, and there is an influence of business capital and entrepreneurial behavior on business success as indicated by the probability value of the F test 0.001 which is smaller than α = 0.05.